2020
DOI: 10.1029/2019wr026250
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of GRACE Data on Changes in Total Water Storage Over the Global Land Surface and 60 Basins

Abstract: Launched in May 2018, the Gravity Recovery and Climate Experiment Follow-On mission (GRACE-FO)-the successor of the erstwhile GRACE mission-monitors changes in total water storage, which is a critical state variable of the regional and global hydrologic cycles. However, the gap between data of the two missions is breaking the continuity of the observations and limiting its further application. In this study, we used three learning-based models, that is, deep neural network, multiple linear regression (MLR), an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
105
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 170 publications
(109 citation statements)
references
References 108 publications
3
105
1
Order By: Relevance
“…To reduce the limitation of remote sensing monitoring data, physics‐based models and data‐driven machine learning models were introduced to predict lake changes (Z. Sun et al., 2020). Cai et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To reduce the limitation of remote sensing monitoring data, physics‐based models and data‐driven machine learning models were introduced to predict lake changes (Z. Sun et al., 2020). Cai et al.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the machine learning approach has been widely applied to hydrological prediction (Humphrey & Gudmundsson, 2019; F. Li et al., 2020; Z. Sun et al., 2020). For example, S Zhu et al.…”
Section: Introductionmentioning
confidence: 99%
“…Note that even though precipitation and temperature are already part of the inputs to global land surface models, they may represent certain aspects of observed climatology that are not fully captured in the simulated TWS (Sun et al., 2019). In addition, the ERA5‐Land forcing data are not identical to the GLDAS forcing data, thus representing a slightly different source of information (Sun & Tang, 2020; Sun et al., 2020).…”
Section: Datamentioning
confidence: 99%
“…Sun et al. (2020) trained and compared the efficacy of three different machine learning (ML) algorithms on reconstructing the TWSA data. They showed that all three regression models perform reasonably well in humid and low‐intensity irrigated areas, but vary significantly in dry and/or intensively irrigated regions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation